HUMAN RESOURCE SYSTEM MUST BE REPLACED BY OPD-SHRM (ONGOING PROFESSIONAL DEVELOPMENT STRATEGIC HUMAN RESOURCE MANAGEMENT) - Diwakar, Shalini; Singh, Panchali (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Old HR system based on profile while OPD-SHRM based on skills. The origin of Ongoing Professional Development is the evaluation of human psychology based totally on human behavior. The OPD concept is based primarily on the validation of the Herzberg hygiene-motivator theory, with OPD providing the motivators. Similarly, creating clear frames of recreation plans in a person's mind and then running with the person to find flow and have fun while turning in the best actions parallels. It instructs HR to rethink employee considerations in a new light so that they can yield greater results. Ongoing Professional Development is a novel way to consider the relationship that exists between an organization and its employees. Currently, HR practices are based on hundred-year-old models that are both powerful and ineffective. OPD is a complicated concept, unlike modern-day ones, that is supported by new technological advancements and is based on scientific proofs. After the OPD concept was implemented on clients in New Zealand, the results were tremendous and superior to those of traditional HR practices. When combined with Human Resource Practices, the OPD theory creates the OPD-SHRM system.